Electronic and interface state density properties of Cu/n-Si MIS-type diode - Yakuphanoğlu, Fahrettin (Elsevier Science Bv, 2007)
Electronic and interface-state density properties of the Cu/n-Si diode were investigated by current-voltage and capacitance-voltage (C-V) analyses. The electronic parameters such as barrier height, ideality factor and series resistance of the diode were determined by performing different plots. The barrier height, ideality factor and series resistance values of the diode were found to be 0.69 eV, 5.31 and 7.63 k Omega, respectively. The obtained ideality factor confirms that the Cu/n-Si device has a metal-insulator-semiconductor (MIS) configuration. The conductance mechanism of the Cu/n-Si diode is in agreement with typical of hopping conduction in polycrystalline and amorphous materials. The interface state density of the diode was found to vary from 1.45 x 10(13) (eV(-1) cm(2)) at E-C-0.45 eV to 0.88 x 10(13) (eV(-1) cm(2)) at E-C-0.66eV. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: MIS diode; interfacial state density; series resistance; AC conductance